Analisis Penerapan Pencatatan Akuntansi berdasarkan SAK EMKM pada UMKM (Studi Kasus Charlie Tani & Petshop) - Sudarlan, Sudarlan; Permana, Diyah; Datu, Ema Farida Tandi (Jurnal EKSIS, 2024)
This study aims to determine the accounting records at Charlie Tani & Petshop MSMEs based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The research method used is quantitative method with primary and secondary data sources. Data collection techniques are carried out by means of interviews, observation, and documentation. The analysis technique used is descriptive analysis by building the application of the accounting cycle and the analysis tool is used based on SAK EMKM. The results showed that accounting records in this business are still simple and not in accordance with accounting standards properly, so that they have not produced appropriate and adequate financial information based on SAK EMKM.